The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1080/07438140509354434
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Nutrients and Turbidity in the Control of Phytoplankton in a Large Western Canadian Lake Prior to Major Watershed Impoundments

Abstract: Northcote, T.G., F.R. Pick, D.B. Fillion and S. Salter. 2005. Interactions of nutrients and turbidity in the control of phytoplankton in a large Western Canadian lake prior to major watershed impoundments. Lake and Reserv. Manage. 21(3):261-276.Kootenay Lake is a large (over 392 km 2 ) fjord-type lake, part of the upper Columbia River Basin, which has undergone significant limnological changes due to a range of human activities over the past half century. We analyzed the limnological conditions of the lake dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Columbia is reported to be P-limited despite substantial anthropogenic P inputs (Northcote, Pick, Fillion, & Salter, 2005), whereas Flathead Lake, Montana, is co-limited by N and P (Spencer & Ellis, 1998).…”
Section: Although Relatively Unstudied On the Pacific Coast Of Northmentioning
confidence: 99%
See 1 more Smart Citation
“…Columbia is reported to be P-limited despite substantial anthropogenic P inputs (Northcote, Pick, Fillion, & Salter, 2005), whereas Flathead Lake, Montana, is co-limited by N and P (Spencer & Ellis, 1998).…”
Section: Although Relatively Unstudied On the Pacific Coast Of Northmentioning
confidence: 99%
“…Pacific Northwest watersheds are generally characterised by relatively high nutrient enrichment with the forested region of the west side of the Cascade Mountains contributing more N and geologic material and the eastside of the Cascade Mountains generating more P (Wise & Johnson, ). In the upper Columbia Basin, Kootenay Lake, British Columbia is reported to be P‐limited despite substantial anthropogenic P inputs (Northcote, Pick, Fillion, & Salter, ), whereas Flathead Lake, Montana, is co‐limited by N and P (Spencer & Ellis, ). Therefore, there is a need to estimate not only the flux of nutrients from anadromous fishes but their influence on nutrient limitation.…”
Section: Introductionmentioning
confidence: 99%
“…Interactions of nutrients and turbidity in the control of phytoplankton in a large western Canadian lake prior to major watershed impoundments was investigated and it was suggested that on-going efforts to rebuild fisheries through restoration of the pre-dam nutrient loading might not return Kootenay Lake to the spatial and temporal complexity that once existed (Northcote et al, 2005).…”
Section: Responsesmentioning
confidence: 99%
“…Investigations of Kootenay Lake began in the mid-1960s when some effects of eutrophication were noted , Northcote et al 2005. Even earlier, in the mid-1950's, residents were concerned about poor water quality, but it was not until the summer of 1958 that widespread algal blooms first appeared and quickly became annual summer occurrences throughout the 1960s and early 1970s (Ennis 1975).…”
Section: Introductionmentioning
confidence: 99%
“…Kootenay Lake is basically a diatom-dominated lake, and this major group, common in all oligotrophic lakes during spring and fall periods, has responded positively to the historic changes in nutrient loading (Ennis 1975, including the most recent years of lake fertilization that began in 1992 , Northcote et al 2005. The spring increase is usually dominated by Fragilaria spp., especially F. crotonensis, as well as Asterionella formosa and Cyclotella spp., and later in the season by Tabellaria fenestrata.…”
Section: Introductionmentioning
confidence: 99%